1990
DOI: 10.1093/ajcn/52.3.502
|View full text |Cite
|
Sign up to set email alerts
|

Medium-chain-triglyceride lipid emulsion: metabolism and tissue distribution

Abstract: The utilization and distribution of radioactively labeled lipid emulsions were evaluated in Sprague-Dawley rats. Animals received one of three lipid emulsions. Group 1 received [14C]medium-chain-triglyceride (MCT) lipid emulsion, group 2 received a 75%:25% (vol:vol) admixture of [14C]MCT: unlabeled long-chain-triglyceride (LCT) lipid emulsion, and group 3 received only [14C]LCT. The radioactive dose appearing in expired carbon dioxide and various body tissues was monitored over a 24-h period. Results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 19 publications
2
43
0
1
Order By: Relevance
“…The ®nding of a better utilisation of LCT emulsion in cancer patients then suggests that LCT are better substrates for lipid storage than MCTaLCT. In fact MCTaLCT are preffered substrates for lipid oxidation (Lutz et al,1989;Johnson et al, 1990). However, lipid oxidation is reduced by insulinaglucose infusion (see results).…”
Section: Discussionmentioning
confidence: 91%
“…The ®nding of a better utilisation of LCT emulsion in cancer patients then suggests that LCT are better substrates for lipid storage than MCTaLCT. In fact MCTaLCT are preffered substrates for lipid oxidation (Lutz et al,1989;Johnson et al, 1990). However, lipid oxidation is reduced by insulinaglucose infusion (see results).…”
Section: Discussionmentioning
confidence: 91%
“…2, excess acetyl-CoA is also expected to enhance the activity of the malate-citrate shuttle, which transports citrate from mitochondria to the cytosol and transfers reducing equivalents from the cytosol to mitochondria. However, experiments with 14 C-labeled MCT administered intravenously to rats demonstrated that the majority of MCT was retained in the liver and about 90% of the MCT was converted to carbon dioxide within 24 h (Bach and Babayan 1982;Johnson et al 1990). The effect of MCT therapy on citrin deficiency may not occur via enhancement of the malate-citrate shuttle, but via a supply of acetyl-CoA, FADH 2 and NADH to hepatic cells as energy sources.…”
Section: Resultsmentioning
confidence: 99%
“…These characteristics are thought to be responsible for the different rates of fat oxidation for MCT versus LCT. In addition, MCT have been shown to undergo increased oxidation in both animal studies [16,17] and human studies [18 -20]. These reports of increased oxidative capacity have made MCT appealing as a possible adjunct for the treatment of obesity; however, MCT have also been shown to have deleterious effects on the blood lipid profile, causing their use to be less desirable.…”
Section: Introductionmentioning
confidence: 99%